2010
DOI: 10.1186/1471-2148-10-147
|View full text |Cite
|
Sign up to set email alerts
|

Retention of low-fitness genotypes over six decades of admixture between native and introduced tiger salamanders

Abstract: BackgroundIntroductions of non-native tiger salamanders into the range of California tiger salamanders have provided a rare opportunity to study the early stages of secondary contact and hybridization. We produced first- and second-generation hybrid salamanders in the lab and measured viability among these early-generation hybrid crosses to determine the strength of the initial barrier to gene exchange. We also created contemporary-generation hybrids in the lab and evaluated the extent to which selection has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 72 publications
0
35
1
Order By: Relevance
“…It lends support to the notion that outbreeding depression may be a temporary phenomenon (Templeton 1986;Rieseberg et al 1996;Carney et al 2000;Christiansen 2008; but see also Johnson et al 2010) and offers a ray of hope for managers faced with situations where the introduction of genetically divergent individuals may be the only remaining option to bolster a dwindling population. Managers should focus efforts on assessing whether the mixing of populations is likely to result in hybrid persistence or genetic swamping, as results from an additional study show that the amount of divergence between the populations at hand, and the fitness of the individual populations in a particular environment, may have a large influence on the outcome of hybridization (Hwang et al in prep).…”
Section: Resultsmentioning
confidence: 58%
“…It lends support to the notion that outbreeding depression may be a temporary phenomenon (Templeton 1986;Rieseberg et al 1996;Carney et al 2000;Christiansen 2008; but see also Johnson et al 2010) and offers a ray of hope for managers faced with situations where the introduction of genetically divergent individuals may be the only remaining option to bolster a dwindling population. Managers should focus efforts on assessing whether the mixing of populations is likely to result in hybrid persistence or genetic swamping, as results from an additional study show that the amount of divergence between the populations at hand, and the fitness of the individual populations in a particular environment, may have a large influence on the outcome of hybridization (Hwang et al in prep).…”
Section: Resultsmentioning
confidence: 58%
“…In a series of papers, our laboratory has demonstrated that nonnative A. t. mavortium introduced into central California in the 1950s led to the formation of a hybrid swarm in approximately 25% of the range of the federally and state-protected California tiger salamander (A. californiense); another 25% has been invaded by a smaller set (3/68 marker loci) of superinvasive genes that are spreading more rapidly (46,59,60). At both the phenotypic and genetic levels, these hybrids generally have higher fitness than pure native salamanders, raising serious conservation concerns for the endangered A. californiense (61)(62)(63)(64).…”
Section: Hybridizationmentioning
confidence: 98%
“…When introgression accompanies hybridization, dilution of the native gene pool can occur (Abbott, 1992;Johnson JR et al, 2010;Johnson MG et al, 2016), and can result in extinction of the native species (Anttila et al, 1998). Often underrated, human-mediated hybridization is one of the leading causes of biodiversity loss via homogenization of formerly distinct populations or taxa (Muhlfeld et al, 2009).…”
Section: Connectivity and Disturbancementioning
confidence: 99%